The Unwritten Conventions: Gender-Based Role Expectations and Rivalry among Indonesia Army Wives - Puspitosari, Wida Ayu; Purwandi, Edeliya Relanika (UI Scholars Hub, 2020)
This paper deploys an ethnographic research of gender-based role expectation of Indonesia army wives. Its aim is to question wives’ positionality vis-à-vis the military institution and consider the implication for how to understand the unwritten conventions and codes to be army wives itself. This paper asserts that the expectation for wives are culturally gendered role that are different for seniors’ and junior’s army wives. To address these points, we discuss the meaning of gendered roles, then progress through a brief history of military marriage procedures, then discuss current expectations for and perception of army wives. We then evaluate the extent to which gendered role expectations continue to ref lect rivalry among army wives before concluding with assertion about what today’s stereotypes and role expectation say about social progress in Indonesia army.